Drug treatment systems in an international perspective : drugs, demons, and delinquents - Klingemann, Harald, 1948-; Hunt, Geoffrey, 1947- (Sage Publications, 1998)
The first volume to provide access to information on drug treatment systems from a wide cross-section of 20 countries, Drug Treatment Systems in an International Perspective examines the ways in which other countries from around the world have chosen to cope with the spread of illicit drugs. Now health planners and administrators, treatment professionals, researchers, and students can place the development of their own treatment systems in a wider context and can examine the extent to which that development shares common structural features with those of other countries and cultures. Following a comparative discussion of the various countries, the volume addresses three key issues: financing and managing drug treatment, gender issues, and the relationship between alcohol and drug treatment.